Chronic Anemia and the Role of the Infusion Therapy Nurse. Issue 5 (September 2015) - Betcher, Jeffrey; Van Ryan, Velvet; Mikhael, Joseph
<x xml:space="preserve">Abstract</x> Chronic anemia develops over a course of weeks to months and is usually mild to moderate in nature. It is important to understand the etiology of the reduced number of circulating red blood cells to treat the anemia appropriately. Diagnosis is dependent on patient history and laboratory findings, such as complete blood counts, iron studies, a peripheral smear, and occasionally, a bone marrow biopsy. Treatment modalities frequently administered by infusion therapy nurses include treatment of the underlying chronic disease, replacement of deficiencies (iron, vitamin B12, folate, or erythropoietin), or transfusion of red blood cells. Infusion therapy nurses play a vital role in the assessment and delivery of medication therapy to patients with chronic anemia.